Physiology-guided personalized mechanical ventilation to prevent ventilator-induced lung injury - Merola, Raffaele; Battaglini, Denise; Schultz, Marcus J.; Rocco, Patricia R. M. (Frontiers in Medicine, 2026)
Mechanical ventilation is essential for managing acute respiratory failure, yet it carries a significant risk of ventilator-induced lung injury (VILI). Lung-protective ventilation, most notably through the use of low tidal volumes, has improved outcomes in acute respiratory distress syndrome (ARDS), but these conventional strategies do not fully account for the profound heterogeneity of the injured lung or the variability in patient-specific physiology. Although tidal volumes of 4–8 ml/kg predicted body weight (PBW) provide a general reference for limiting strain, truly protective ventilation requires individualization based on regional aeration, compliance, and recruitability. Variability in these parameters leads to uneven distributions of stress and strain, while dynamic changes in respiratory drive, inspiratory effort, and cardiopulmonary interactions further complicate uniform ventilatory management. The mechanisms underlying VILI: barotrauma, volutrauma, atelectrauma, and biotrauma extend beyond the lung parenchyma and contribute to ventilator-associated diaphragm dysfunction and secondary organ injury. Bedside physiological tools, including esophageal manometry, electrical impedance tomography, and lung ultrasound, allow real-time evaluation of lung stress, regional ventilation, recruitability, and patient effort. When incorporated into clinical decision-making, these modalities facilitate individualized adjustments aimed at avoiding overdistension and collapse, limiting injurious pressures and volumes, and maintaining adequate gas exchange and hemodynamic stability. Advances in technology, such as closed-loop ventilation systems, adaptive control algorithms, and computational modeling, offer additional opportunities to refine personalized strategies and anticipate harmful mechanical patterns. Collectively, physiology-guided, personalized mechanical ventilation shifts practice from protocol-driven approaches to patient-centered care, with the overarching goal of mitigating VILI and improving outcomes in critically ill patients.